Direito material coletivo: uma proposta de sistematização jus-filosófica - Cerullo, Alexandre (2008)
This study aims at introducing the community material law in a systematic way and at showing given its nature and particularities it is part of the Brazilian legal system along with the private and public laws, being established as a new branch of law. Thus, this justifies the study due to the need of examining the new Brazilian legal system and to the lack of systematization of the new branch, disclosing common points of the main legislations it comprises, forming a sole body. As a backdrop, the event surveyed takes into consideration the breaking of paradigms and the deficiency of the private and public laws in protecting goods, and collective rights. At the forefront, it proposes and indicates particularities of the community material law that best meet the responses expected by the community that, also due to their nature, are not similar to those of the individuals and the State. Based on that, they become cohesive and are better tools to meet their needs, qualifying it as a new branch of law. The theoretical-methodological procedure proposes its systematization by using the holistic theory of law (holistic philosophy) and shows that the current paradigm is not based on linear or reductionist theories, but that all the social problems faced by the science of law are part of a sole issue: human life s sustainability. This is why the private and public laws are regarded for linear or reductionist questions, and the community material law is regarded as a new branch of law, with unique qualities for holistic matters. Then, the major pieces of collective legislation are examined and compared with the previous paradigms and the current one. The evolution is analyzed as well as an attempt is made in order to categorize the new branch of law. In conclusion, we observe that the community material law complements the Brazilian legal system, forming a trilogy with the private and public laws